Talent Development Research, Policy, and Practice in Europe and the United States: Outcomes From a Summit of International Researchers. (July 2017) - Subotnik, Rena F.; Stoeger, Heidrun; Olszewski-Kubilius, Paula
The goal of this article is to convey a summary of research and conversation on talent development on the part of a small group of European and American researchers who participated in the Inaugural American European Research Summit in Washington. In the final hours of the summit, participants discussed the state of research on talent development and giftedness and a way forward that would benefit the field and, most important, children and educators. Collectively we identified four broad themes: (1) expanding our conceptual horizons through increased exposure to international scholars, (2) shifting the paradigm of gifted education toward talent development, (3) promoting key elements of talent development in research and practice, and (4) finding the most effective policy and advocacy strategies to promote talent development.